Fun English for Young Learners Bagi Anak Anak Tpa Darus Salam Masjid Raudlatut Tholibin Binanga Lingkungan Danga Mamuju - Kurnia; Abdul Wahab (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2023)
English is the most widely used foreign language for the world population today. Schools in Indonesia also teach English as one of the subjects that must be mastered for students starting from elementary, middle, and high school levels. However, not all primary schools teach English, including the primary and kindergarten children who study at TPA Darus Salam Masjid Raudlatut Tholibin, Binanga Village, Danga Neighborhood, Mamuju, West Sulawesi. They admitted that they did not learn English at all at school. This community service aims to teach English by using Fun English Learning Strategies for children at TPA Darus Salam Masjid Raudlatut Tholibin located at Jalan Husni Thamrin Binanga Sub-district Mamuju City West Sulawesi.